Tooth number anomalies and ectopic eruption in a group of pediatric dental patients - EREN GİRAY, FİGEN; ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2022)
Objective: This retrospective study aimed to evaluate the frequency and distribution of tooth number anomalies and ectopic eruption in a group of pediatric dental patients. Matherial and Methods: The CBCT images of pediatric dental patients (6-14-year-old) taken between 2016-2022 were selected from the archive of Marmara University, Faculty of Dentistry. The CBCT images taken with Planmeca Promax 3D Mid (Planmeca Oy, Helsinki, Finland, 2012) were retrospectively re-examined to determine the frequency and distribution of the ectopic tooth, hypodontia, hyperdontia, mesiodens, or other. Descriptive statistics were used for evaluating the registered data. Pearson’s Chi-squared and Fisher exact tests were used for the statistical analysis. Data were statistically analyzed at p<0.05 significance level. Results: Of the 511 pediatric dental patients aged between 6-14-year-old (10.9±2.63), 246 were girls and 265 were boys. Hyperdontia was the most frequently observed number anomaly (12.7%), followed by Hypodontia (9.2%). The frequency of ectopic teeth was 4,9%. The prevalence of hyperdontia was significantly higher in boys (p=0.033). Conclusions: Tooth number anomalies require a detailed radiologic examination and careful treatment planning since those anomalies may lead to or complicate the orthodontic treatment. Based on our findings, it was concluded that high-quality CBCT examinations provided detailed evaluation, revealed a high prevalence of tooth number anomalies and gave information about the current demographic trends.

Amaç: Bu retrospektif çalışmada bir grup pedodonti hastasında diş sayı anomalilerinin sıklığı ve dağılımlarının değerlendirilmesi amaçlanmıştır. Gereç ve Yöntemler: Marmara Üniversitesi Diş Hekimliği Fakültesi arşivinden Planmeca Promax 3D Mid (Planmeca Oy, Helsinki, Finlandiya, 2012) ile 2016-2020 yıllarında çekilmiş 6-14 yaşlar arasındaki çocuk hastalara ait konik ışınlı bilgisayarlı tomografi (KIBT) görüntüleri yeniden incelenmiş ve retrospektif olarak hipodonti, hiperdonti, meziodens, ektopik dişlerin sıklığı ve dağılımı değerlendirilmiştir. Betimleyici istatistiksel analiz, Pearson ki-kare ve Fischer kesin olasılık testleri kullanılmıştır. Bulgular: Pedodonti hastalarının 246’sını kız ve 265’ini erkek hastalar oluşturmuştur (n=511). Hiperdontinin (% 12.7) en sık rastlanan diş sayı anomalisi olduğu ve bunu hipodontinin (%9.2) takip ettiği belirlenmiştir. Ektopik dişlerin görülme sıklığı % 4.9 olarak kaydedilmiştir. Hiperdonti prevalansının erkek çocuklarda istatistiksel olarak anlamlı şekilde yüksek olduğu saptanmıştır (p=0.033). Sonuçlar: Diş sayı anomalileri ortodontik tedavi gerektirebileceğinden detaylı radyolojik inceleme ve dikkatli bir tedavi planlaması gerektirmektedir. Çalışmanın bulguları yüksek kaliteli KIBT görüntülerinin detaylı değerlendirme imkanı vererek diş sayı anomalilerindeki yüksek prevalansı ortaya çıkarmış ve güncel demografik eğilimler hakkında bilgi vermiştir
Keywords: Hipodonti; Hiperdonti; Diş Sayı Anomalisi; Konik Işınlı Bilgisayarlı Tomografi; Hypodontia; Hyperdontia; Cone-Beam CT; Tooth number anomaly